Spectral features of Ho3+ -doped boro-phosphate glass-ceramics: Role of Ag nanoparticles sensitization - Alqarni, Areej S. (Elsevier B. V., 2020)
The development of the metallic nanoparticles-sensitised and lanthanides-doped multi-functional luminescent glass-ceramics (GCs) for advanced applications remains challenging. In this perception, the role of varying silver nanoparticle (Ag NP) concentration on the structures, microstructures and optical properties of some new class of zinc-sulfo-boro-phosphate GCs activated with holmium ions (Ho3+) was analysed using different mechanisms. These GCs were prepared by the standard melt-quenching and thoroughly characterised using various analytic means. The XRD patterns of the as-quenched samples confirmed their GC nature. The Judd–Ofelt (J–O) intensity parameters and radiative properties plus the CIE colour coordinates for these GCs were evaluated using the measured photoluminescence (PL) spectral data. The absorption spectra of the GCs revealed 13 peaks associated to the Ho3+ transitions and the absorption edge data were used to calculate the optical band gap and Urbach energy. The PL spectra of the titled GCs revealed an intense green and red emission peak distinctive of the electronic transitions in Ho3+. Despite the strong mediation of the Ag NPs LSPR on the PL emission of Ho3+, the structural alterations in the GCs network played a dominant role towards the PL peak intensity quenching. The density, Raman, FTIR and impedance spectral analyses exhibited the formation of more bridging oxygen and significant reduction of the nonbridging oxygen in the GC matrix due to the addition of Ag NPs, leading to the Ho3+ clustering. An interrelationship between the structural and optical attributes in these GCs was ascertained for the first time. The proposed GC compositions are established to be beneficial for the advancement of the novel luminescent materials for various photonic and optoelectronic applications.